Library Web Portals in Knowledge Management at UASB - A Case Study - Naika, K. Venkataranga; D.M. Suneel; B. M. Puneeth; N. Kavya; Pooja; B.L. Gurumurthy (Journal of Agricultural Extension Management, 2021)
The UAS Library’s birth dates back to the collection in the Department of Agriculture (which was established in 1899, and a significant share of this Library was taken away by the Agricultural Library, Hebbal, in 1946), which forms the nucleus of the present UAS Library. This paper traces the services available at the University of Agricultural Sciences, Bengaluru; specifically, this paper aims to illustrate the knowledge management service provided by UASB to the faculty and students and document web portals available to the users in general. Services available at the University of Agricultural Sciences, Bengaluru include useful Web Portals such as OAPEN: Online Library and Publication Platform, Kidrex, and DOAB. In the wake of changing times and the technology revolution, it is an axiom to note that knowledge management calls for integrating e-resources web portals besides books, Journals & open/paid sources to augment users’ knowledge in the years to come.